Phase-field simulations of electrohydrodynamic jetting for printing nano-to-microscopic constructs. Issue 42 (30th June 2020) - Singh, Sachin K.; Subramanian, Arunkumar
Abstract : This paper simulates the transient evolution of an electrohydrodynamic jet and reveals the dependence of its characteristics on the underlying process parameters. Abstract : A numerical simulation is presented for predicting the transient ejection of micro-/nano-scopic jets from microscale nozzles, when a liquid confined within the nozzle is subjected to an external electric field. This simulation is based on the Taylor–Melcher leaky dielectric model, and uses the phase field method for interface tracking. The presented model is able to successfully simulate the deformation of a flat liquid meniscus into a Taylor cone, eventually leading to jet formation and breakup into droplets. Several simulations are performed to understand the effect of process parameters like applied voltage, liquid flow rate and properties on jet ejection dynamics. The results reveal the dependence of the ejected jet diameter and current primarily on the applied electric potential, liquid flow rate and electrical conductivity of the liquid. For high conductivity liquids, it is found that the convection current is of the same order of magnitude as the conduction current. In contrast, the convection current dominates the conduction current during jet ejection in the case of low conductivity liquids, regardless of the flow rate. It is also found that stable jets smaller than 200 nm can be produced from a 2 μm nozzle, which would facilitate patterning structures at the nanoscale. This model presents an approach to analyze the effect of process parameters on electrojet ejections and can effectively guide the design of printheads for e-jet systems that pattern nanoscale features in jetting and nano-dripping modes from microscopic nozzles.